Integrating agricultural research into an African innovation system - Lynam, John K.; Methu, Joseph; Waithaka, Michael (International Food Policy Research Institute, 2016)
This chapter explores the potential for organizing African agricultural research within an AIS framework. The first section evaluates the principal issues involved within the specific context of the region. The second section presents a concrete example of the approach in the form of a case study. Thereafter, the principal methodologies for bringing about this kind of organizational transformation are reviewed. Finally, existing examples of the region’s use of the AIS approach are reviewed to explore lessons learned to date.